2017
DOI: 10.1093/gigascience/gix133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cPAS-based BGISEQ-500 platform for metagenomic sequencing

Abstract: BackgroundMore extensive use of metagenomic shotgun sequencing in microbiome research relies on the development of high-throughput, cost-effective sequencing. Here we present a comprehensive evaluation of the performance of the new high-throughput sequencing platform BGISEQ-500 for metagenomic shotgun sequencing and compare its performance with that of 2 Illumina platforms.FindingsUsing fecal samples from 20 healthy individuals, we evaluated the intra-platform reproducibility for metagenomic sequencing on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
160
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 16 publications
0
160
0
Order By: Relevance
“…DNA extraction of cervical samples and fecal samples was performed as described (Chen et al, 2017; Li et al, 2014). Metagenomic sequencing was done on the BGISEQ-500 platform, which is highly comparable to Illumina HiSeq platforms in metagenomic and other sequencing applications (Fang et al, 2018; Han et al, 2018; Li et al, 2018; Pan et al, 2018). 50bp of singled-end reads for cervical samples collected in the initial study cohort, and on average 208.76 million raw reads were sequenced for each sample (Table S1B); 100bp of singled-end reads for fecal samples collected in the initial study cohort, and on average 85.63 million raw reads were sequenced for each sample (Table S1B); 100bp of paired-end reads for cervical samples, fecal samples and saliva sample collected in the second cohort, and on average 158.91 million raw reads, 75.84 million raw reads were sequenced for each cervical sample and saliva sample, respectively (Table S1B).…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction of cervical samples and fecal samples was performed as described (Chen et al, 2017; Li et al, 2014). Metagenomic sequencing was done on the BGISEQ-500 platform, which is highly comparable to Illumina HiSeq platforms in metagenomic and other sequencing applications (Fang et al, 2018; Han et al, 2018; Li et al, 2018; Pan et al, 2018). 50bp of singled-end reads for cervical samples collected in the initial study cohort, and on average 208.76 million raw reads were sequenced for each sample (Table S1B); 100bp of singled-end reads for fecal samples collected in the initial study cohort, and on average 85.63 million raw reads were sequenced for each sample (Table S1B); 100bp of paired-end reads for cervical samples, fecal samples and saliva sample collected in the second cohort, and on average 158.91 million raw reads, 75.84 million raw reads were sequenced for each cervical sample and saliva sample, respectively (Table S1B).…”
Section: Star Methodsmentioning
confidence: 99%
“…50bp of singled-end reads for cervical samples collected in the initial study cohort, and on average 208.76 million raw reads were sequenced for each sample (Table S1B); 100bp of singled-end reads for fecal samples collected in the initial study cohort, and on average 85.63 million raw reads were sequenced for each sample (Table S1B); 100bp of paired-end reads for cervical samples, fecal samples and saliva sample collected in the second cohort, and on average 158.91 million raw reads, 75.84 million raw reads were sequenced for each cervical sample and saliva sample, respectively (Table S1B). Quality control and alignment to GRCh38 was performed as previously described (Fang et al, 2018; Li et al, 2018).…”
Section: Star Methodsmentioning
confidence: 99%
“…collected at Shenzhen people`s Hospital, transported frozen, and extracted at BGI-Shenzhen [12]. The BMD was calculated by Hologic dual energy X-ray machine at Shenzhen people`s Hospital.…”
Section: Study Cohort and Sample Information Fecal Samples And Clinimentioning
confidence: 99%
“…Moreover, the transplantation of fecal or specific bacteria to specific pathogen free (SPF) mice or germ-free mice also showed that the gut microbiota could also modulate the bone homeostasis by immune system modulating and osteoclast formation [10]. But most of these experiments [7,11] were carried on mice and 16S sequencing which is poor taxonomic resolution, low sensitivity and no functional related information [12].Notably, the metagenome-wide association studies (MWAS) based on the human shotgun sequencing which could reveal the relationship between the bone mass loss and the microorganisms [13].…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, it is not currently possible to obtain full information about sequencing by MGISEQ-2000. A couple of years ago, a paper was published demonstrating a similar accuracy of SNP detection and a slightly lower accuracy of indel detection for the BGISEQ-500 platform, as compared to HiSeq 2500, using a reference genomic dataset from GIAB [3]. A few recent studies have compared the performance of these two platforms in sequencing ancient DNA [10], metagenome [11] and microRNA [4]. In general, the quality of data generated by BGISEQ-500 has proved to be good, although some of its characteristics are somewhat worse than those of Illumina HiSeq 2500.…”
Section: Introductionmentioning
confidence: 99%